40.5k views
5 votes
✓13 + 34 + 25. 2((2• 3)2 - 2 • 45) 9

✓13 + 34 + 25. 2((2• 3)2 - 2 • 45) 9-example-1
User Kern
by
5.7k points

1 Answer

2 votes

SOLUTION

Given the expression


\frac{\sqrt[]{13+3^4+25*2}}{((2*3)^2-2*45)/9}

We can find the solution by simplifying the question.


\begin{gathered} \frac{\sqrt[]{13+3^4+25*2}}{((2*3)^2-2*45)/9} \\ =\frac{\sqrt[]{13+81^{}+50}}{((2*3)^2-2*45)/9} \\ =\frac{\sqrt[]{13+81^{}+50}}{(6)^2-90)/9} \\ =\frac{\sqrt[]{144}}{(36-90)/9} \\ =(12)/(-54/9) \\ =(12)/(-6) \\ =-2 \end{gathered}

Answer: -2

User Recursive
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.